ANALISIS KESULITAN MENGAPLIKASIKAN MYOB ACCOUNTING PESERTA DIDIK KELAS XII AKUNTANSI SMKN 1 SUNGAI RAYA - Reni Hardianti; Bambang Genjik S; Warneri Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe purpose of this research is to find out what's causing the trouble to apply MYOB Accounting to class XII Accounting major for Country’s Vocational High School 1 Sungai Raya. This research is based on a troubling finding by an author during the Accounting for the difficult implementation of MYOB Accounting. The experimental method used in this study is a descriptive method with a qualitative approach and a form of survey research. The source of data in this study is 15 Accounting students, teachers of subjects and utilities and facilities. The data-collection tool on this research is the documentation paperwork and the pedophile interviews. The analtic technique of data on this research is domain analysis. The results of this research can be concluded that the causes of the trouble of applying MYOB Accounting to class xii Accounting for 1 bengkacia-district regional river Accounting for internal factors (1) psychological (a) attitudes (b) talent (c) motivation. (2) skills and abilities. External factors (1) family environment factors (2) school environmental factors.Keywords: Accounting Difficulties Learning, MYOB